2016
DOI: 10.1083/jcb.201601050
|View full text |Cite
|
Sign up to set email alerts
|

Tissue homogeneity requires inhibition of unequal gene silencing during development

Abstract: Homogenous populations of cells make up individual tissues, yet how organisms achieve such homogeneity is unknown. Le et al. use the C. elegans intestine to reveal that an initiator of RNA silencing is segregated unequally between cells. Suppression of this inequality during early development achieves tissue homogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…While many genes do not require NRDE-3 for silencing, the bli-1 gene requires NRDE-3 for silencing by ingested dsRNA or neuronal dsRNA (13). Finally, a strict requirement for NRDE-3 but not for RRF-1 is seen for the silencing of repetitive DNA that occurs in an enhanced RNAi background upon growth at lower temperatures (30). These observations suggest that a mix of mechanisms could underlie RNAi in C. elegans.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…While many genes do not require NRDE-3 for silencing, the bli-1 gene requires NRDE-3 for silencing by ingested dsRNA or neuronal dsRNA (13). Finally, a strict requirement for NRDE-3 but not for RRF-1 is seen for the silencing of repetitive DNA that occurs in an enhanced RNAi background upon growth at lower temperatures (30). These observations suggest that a mix of mechanisms could underlie RNAi in C. elegans.…”
Section: Introductionmentioning
confidence: 93%
“…This target is a multicopy transgene that generates trace amounts of dsRNA that can cause selfsilencing in enhanced RNAi backgrounds (e.g. adr-1(-); adr-2(-) in (55) and eri-1(-) or rrf-3(-) in (30)). Silencing by this target-derived dsRNA was modest ( Figure 1A, ~24 GFP+ nuclei in eri-1(-), p-value < 10 -3 when compared to ~30 GFP+ nuclei in eri-1(+)), consistent with earlier reports (11,30).…”
Section: Silencing By Neuronal Dsrna Can Be Distinct From Silencing Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Once a tissue has been specified, however, its constituent cells must remain similar to each other, even as they continue to divide and, by chance, segregate their components unequally to their daughter cells. now identify a mechanism that helps maintain tissue homogeneity during C. elegans development (1). …”
mentioning
confidence: 99%
“…Jose and colleagues, led by undergraduate Hai Le, first investigated how the sur-5::gfp transgene is silenced, and found that dsRNA produced from the repetitive array is processed through the canonical RNAi pathway and the nuclear Argonaute protein NRDE-3 (1). The silencing was locus specific: the sur-5::gfp array could be silenced in intestinal cells that still showed expression from other repetitive transgenes or single-copy GFP inserts.…”
mentioning
confidence: 99%